Development of Social Competence in High School Students in the Context of Non-Formal Education - Chaikovska, Hanna; Levchyk, Iryna; Fedoruts, Mykola; Polishchuk, Vira; Mazur, Oksana (Acta Paedagogica Vilnensia, 2023)
The paper describes an issue of development of social competence in high school students in the context of non-formal education. The research experiment involved 647 high school students from seven Ukrainian secondary comprehensive schools in Ternopil and Ivano-Frankivsk regions. The diagnostic methods, applied at the pre-experiment stage, were specified with key components of social competence structure. The corresponding criteria, indicators and descriptive scale of levels of formation were substantiated and characterised. Findings of the diagnostic survey indicated a significant lack of social competence of a future school graduate.The necessary socio-pedagogical conditions of realisation of the main provisions of non-formal education, were introduced in the course of the experiment from September 2017 until June 2019. They implied stimulation of the subjective position of a student, provided socio-pedagogical support and monitoring, modernisation of content, forms and methods of non-formal education, organisation of amateur space and support. Various forms of realisation of non-formal education resulted in significant positive shift of development of social competence in participants of experimental groups.The comparative correlation of post-experiment survey estimated increase in number of students with high level of social competence up to 15% and decrease in number of respondents with low level up to 11%. Final analysis of the obtained data verified the hypothesis of the research and proved the significance of shifting focus to non-formal type of education from the formal type in development of social competence in high school students.